Twin Peaks. The second season [videorecording (DVD)] - Lynch, David, 1946-; Frost, Mark, 1953- (Paramount Home Entertainment : CBS DVD, 2007)
FBI Special Agent Dale Cooper is back once again to solve the case of who killed Laura Palmer in the sleepy Washington town of Twin Peaks.